Formation of a gas-discharge plasma active medium on Kr2F* trimers; Optics Communications; Vol. 356 - Panchenko Yu.N. Yury Nikolaevich; Andreev M. V. Mikhail Vladimirovich; Losev V. F. Valery Fedorovich; Puchikin A. V. Aleksey Vladimirovich (2015, 2015)
Title screen